On the multilinear generalizations of the concept of absolutely summing operators - Caliskan, Erhan; Pellegrino, Daniel M. (ROCKY MT MATH CONSORTIUM, 2007)
In this paper we investigate the several multilinear generalizations of the concept of absolutely summing operators and their connections. We also introduce the concept of p semi-integral mappings and establish the position of p semi-integral mappings with respect to the other classes.
Keywords: POLYNOMIALS; Mathematics